Oxidative Stress in Patients with Type 2 Diabetes Mellitus - Shakir Khan ,Abdul Khaliq Naveed ,Faizania Shabbir,Tausif Ahmed Rajput ,Muhammad Javad Yousaf (Journal of Rawalpindi Medical College, 2014)
Background : To assess the reduced glutathione (GSH) levels as marker of oxidative stress in patients of diabetes mellitus Methods: In this cross sectional study 40 subjects were divided into two groups. One group was designated as control while the other was diabetic. Glycemic status was measured to confirm their normal and diabetic states respectively. Plasma reduced GSH level was measured by using standard ELISA kits. Results: Level of reduced GSH was decreased in the diabetic group (18.4 ± 1.35) as compared to the control group(27.5 ± 1.38). Conclusion: Levels of reduced GSH were significantly decreased in patients of diabetes mellitus as compared to normal healthy controls